Financial development, FDI, and economic growth in low-and middle-income countries: a dynamic panel threshold - Sirag, Abdalla; Ali, Hamisu Sadi; Lacheheb, Zakaria; Ahmed, Osman Sirajeldeen; Omer, Emad Eldin (Ital Publication, 2025)
The study investigates the nonlinear relationship between financial development and economic growth, with a particular focus on the mediating role of FDI in low- and middle-income countries. Using annual panel data covering 81 countries from 1990 to 2019, the study applies a dynamic panel threshold regression model to identify the level of financial development at which its impact on economic growth changes. The analysis incorporates FDI as an additional conditioning variable to examine how its interaction with financial development influences the threshold dynamic. A significant threshold effect: below a certain level of financial development, the impact of FDI on growth is statistically insignificant, while above the threshold, FDI exerts a strong positive influence on economic growth. The findings imply that the growth-enhancing effect of financial development is not automatic and depends on reaching a critical level of financial maturity, as well as an enabling environment that leverages FDI inflows. The study contributes to the literature by offering empirical evidence of a nonlinear, FDI-conditioned finance-growth nexus, and it provides policy guidance for developing economies aiming to optimize the benefits of financial sector reforms.